UKRAINIAN ETHNIC ELEMENTS IN THE DESIGN OF A MODERN HOTEL INTERIOR: ORIGINS AND FEATURES - Михайлова, Р. Д.; Плисюк, Ю. О. (Art and Design, 2020)
To analyze Ukrainian ethnic elements in interior design. Based on the consideration of relevant samples, to reveal the origins and features of the elements that are used in the artistic and aesthetic organization of the hotel interiors designed in Ukrainian style. To determine the basic concepts in the article, there is a method of terminological and semantic analysis applied. Sources on the topic of research, normative scientific and methodological documentation are reviewed with the methods of comparative analysis. For historical sources the chronological method is used. Domestic and foreign implementations and operations of projects are examined with elements of a critical analysis. The systematization of materials is based on the methods of analysis and synthesis. This paper analyzes elements of Ukrainian artistic culture in hotel interior design. Ethnic elements in hotel design have been identified as having important functions – informative, informative, aesthetic, decorative, historical, cultural, educational and educational. In the conditions of military confrontation for many Ukrainians the ethno-national style of the interior, formed through the targeted selection of folk elements and motifs, also acquires a patriotic color. Such semantic expressiveness contributes to the active dissemination of design in ethno-national stylistics both in the field of housing interior and commercial premises. Thіs study identified the source of inspiration source of inspiration for creating interiors using ethnic elements and motifs is Ukrainian folk culture. Its diversity is presented in the works of folk architecture, fine and decorative art, amateur works of folk artists, as well as their stylization by professional artists. In the study, the author concludes that interior design in folk style using elements of the artistic and material culture of Ukraine is a kind of guarantee of the preservation of its ethnocultural identity as the basis of national identity in modern architecture and the architectural environment. Scientific novelty of the results obtained is to identify the specifics of the use of Ukrainian ethnic elements in the modern hotel interior, and, in general, the modern principles of the formation of ethnic style, the disclosure of its semantic and semantic meaning, justification of its feasibility and aesthetic appeal through the use of appropriate design stylistics. The results can be used in design practice, as well as to achieve consistency and efficiency in the organization of the hotel interior.